Social Media and Tourist Behavior : A Quantitative Study on The Relationship Between Travel Experience Sharing and Travel Intention - I Made Juniawan; Dewi, Luh Gede Leli Kusuma (Graduate School, Universitas Brawijaya, 2024)
Social media has become a primary source of travel information, where user-generated content is perceived as more reliable than information from tourism organizations. With young users dominating social media platforms, this phenomenon has reshaped tourist behavior, as they seek destinations not only to visit but also to document and share. A deeper understanding of this relationship will provide valuable insights for the tourism industry in designing effective marketing strategies and enhancing engagement with travelers. This study examines the influence of travel experience sharing on social media on tourists' visit intentions, particularly among youth travelers. The informants selected by incidental sampling technique focus on domestic tourists. Using a quantitative approach in regression analysis, five key determinants were identified. This study also finding there is a positive and significant effect of travel experience sharing on travel intention of tourist. The travel experience sharing affects 41.7 percent on travel intention. While remaining 58.3 percent is explained by other variables not involved in this study. Social; Media; Travel; Intention; Experience; Share; Youth